Climatic suitability of Dichrorampha odorata Brown and Zachariades (Lepidoptera: Tortricidae), a shoot-boring moth for the biological control of Chromolaena odorata (L.) R.M. King and H. Robinson (Asteraceae) in South Africa - Nqayi, Slindile Brightness (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
Biological control using natural enemies introduced from the native range is an integral component of the management of Chromolaena odorata, a serious invader in the eastern regions of South Africa. A number of biological control agents for C. odorata have been released in South Africa, and one of them, Dichrorampha odorata, has failed to establish. To understand if D. odorata failed to establish due to climate incompatibility, its thermal physiology was investigated. Thermal tolerance data were used to determine the developmental thresholds and number of generations that D. odorata is capable of going through in South Africa per year. These predictions were generated using CLIMEX temperature data and the degree-day parameters K and t0. Developmental time decreased with increasing temperatures ranging from 20 °C to 30°C, with immature stages not able to complete development at 18°C and 32°C. The developmental threshold, to, was determined as 8.45 °C with 872.4 degree-days required to complete development (K), indicating that D. odorata is capable of producing a maximum number of 6.5 generations per year in South Africa. The CLIMEX data indicated that the east coast regions of South Africa, which are the heaviest invaded areas by C. odorata in South Africa, were climatically most suitable for D. odorata to. D. odorata lower (LLT50) and upper (ULT50) lethal temperatures were -4.5°C and 39.64°C for larvae and 1.83 and 41.02°C for adults, and D. odorata adults were able to maintain locomotory functioning at 4.4 to 43.7°C, respectively. Acclimation at low and high temperatures indicate that when D. odorata was kept at a lower temperature of 20°C for 7 days, it became tolerant to warmer and cooler temperatures (1.95 and 44.41°C) when compared to D. odorata reared at 25°C (3.36 and 43.67°C) and 30°C (5.92 and 42.93°C). Dichrorampha odorata is therefore climatically suitable for release and should establish in South Africa to control C. odorata. The establishment and persistence of D. odorata will not be limited by climatic conditions but rather the distribution of its host weed, C. odorata in South Africa. Also, this study presents a decision-making protocol for the release of D. odorata to allow better performance in the field.
Keywords: CLIMEX; Chromolaena odorata -- Biological control -- South Africa; Tortricidae -- South Africa; Bioclimatology -- Software